2001
DOI: 10.1111/1469-8986.3850828
|View full text |Cite
|
Sign up to set email alerts
|

Time‐of‐day variations in different measures of sleepiness (MSLT, pupillography, and SSS) and their interrelations

Abstract: The aim of the present study is to analyze how well physiological measures of sleepiness derived from pupillography and the Multiple Sleep Latency Test correlate with a subjective measure, the Stanford Sleepiness Scale (SSS) score. The results are based on data from 12 healthy participants, who underwent these tests every 2 hr from 7:00 a.m. until 11:00 p.m. Sleep latencies were correlated with four different variables derived from pupillography and the SSS score. The results indicate that the physiologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
40
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 14 publications
7
40
1
5
Order By: Relevance
“…However when RPUI, which is a default output of the portable electronic pupillometer F2D, is used, it is advisable to adjust RPUI by PD in the inter-individual comparisons. PD correlated neither with SL nor ESS, indicating that this pupillometric parameter is not suitable for detecting inter-individual differences in sleepiness, while in intraindividual circadian variations [16], it correlated well with MSLT-derived sleepiness, which seems to reflect the same aspect of the level of tonic central nervous activation. Morrell [23] indicated that both SL and ESS reduced with age in patients with moderate-to-severe sleep disordered breathing, and Eggert [24] found PUI and PD to decrease with increasing age in healthy subjects.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…However when RPUI, which is a default output of the portable electronic pupillometer F2D, is used, it is advisable to adjust RPUI by PD in the inter-individual comparisons. PD correlated neither with SL nor ESS, indicating that this pupillometric parameter is not suitable for detecting inter-individual differences in sleepiness, while in intraindividual circadian variations [16], it correlated well with MSLT-derived sleepiness, which seems to reflect the same aspect of the level of tonic central nervous activation. Morrell [23] indicated that both SL and ESS reduced with age in patients with moderate-to-severe sleep disordered breathing, and Eggert [24] found PUI and PD to decrease with increasing age in healthy subjects.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, the association between pupillometry and MSLT could not be adjusted for the time-of-day effects [13,16] in this study.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Erste Hinweise auf die zu erwartenden Größenordnungen des Risikos, im Zuge einer einzelnen Risikoexposition (z. [5,15,22,23,26,33,35,39]) und F subjektive Schläfrigkeitsskalen [19,28,38,39,40]. …”
unclassified
“…Die Validität des PST wurde durch eine Reihe von Validierungskriterien bestätigt: F Medikation mit (De-)Aktivierungsinduktion [10,11,30], F mit Schläfrigkeit assoziierte, klinische Störungsbilder [43], F zirkadiane Verläufe [28,39,42], F physiologische Parameter (z. B. Elektroenzephalographie, EEG; [24]), F Multipler Schlaflatenz-Test (MSLT; [5,15,22,23,26,33,35,39]) und F subjektive Schläfrigkeitsskalen [19,28,38,39,40]. …”
unclassified